Supreme Court hearing on "Neither confirm nor deny" policy: A landmark case for state secrecy (International Federation for Human Rights, 2025)
On 11 June 2025, the United Kingdom Supreme Court heard the Secretary of State for Northern Ireland’s appeal against a Coroner’s decision to disclose a gist of information in the inquest into the 1994 sectarian murder of Paul "Topper" Thompson by loyalist paramilitaries in Belfast, in which there is suspected state collusion.
Ireland